Development of emulsified wastewater treatment system - Hon Yvain, Chong (2014)
Emulsions are commonly used in metal processing productions as emulsified coolant and lubricating oil. These emulsions will be discharged off as emulsion waste after losing their efficiency. These wastes have to be treated to satisfy the standard limits before being discharged to waterways to prevent pollutions. This work targets to develop an emulsified wastewater treatment system using effective bio-coagulant and low cost agricultural waste as bio-adsorbent. Chitosan and rubber seed shell activated carbon (RSSAC) as bio-coagulant and bio-adsorbent respectively will be employed in this work. Samples of emulsified wastewater were collected and analysis was done. Activation of chitosan powder was prepared by diluting it with acetic acid and distilled water. The fresh rubber seed was cracked to get the shell which was then washed, sun-dried, pulverised and sieved and impregnated with NaOH before carbonization to produce RSSAC. Carbonization was able to increase the SBET up to 20 folds. Results show the highest reading of SBET (19.2403m2/g) at 650oC compared to SBET (0.9482m2/g) before carbonization. Carbonization is able to remove volatile compounds and promotes formation of new pores. However, the SBET dropped at high temperature 850oC because of surface erosion and rupture of some porous wall which causes lower porosity formation. Jar test method was used with chitosan as coagulant at primary treatment followed by RSSAC as adsorbent at secondary treatment. Effects on removal of oil & grease (O&G), total suspended solids (TSS), turbidity and pH value were studied in this paper by varying the contact time and dosage. The combined system able to reduce 90% of O&G compared to chitosan alone which only able to reduce up to 76%. The chitosan able to agglomerate and demulsify emulsion and improve the residual oil coagulation. Further addition of RSSAC able to adsorb the remaining oil left from the primary treatment. The treatment is able to reduce TSS and turbidity up to 98.7% and 92.5% respectively. Treated wastewater can be further processed by using membrane ultrafiltration to remove residual RSSAC. Also, the colour indicates the presence of heavy metals and can be further treated to improve filtrate clarity. RSS may be further explored into producing activated carbon by other means of activation and used adsorb other types of substance such as dyes, heavy metals and other impurities. Present work is able to treat emulsion waste by using effective bio-coagulant and low cost industrial waste as bio-adsorbent